Catechol-based matrix metalloproteinase inhibitors with additional antioxidative activity. (4th November 2016) - Tauro, Marilena; Laghezza, Antonio; Loiodice, Fulvio; Piemontese, Luca; Caradonna, Alessia; Capelli, Davide; Montanari, Roberta; Pochetti, Giorgio; Di Pizio, Antonella; Agamennone, Mariangela; Campestre, Cristina; Tortorella, Paolo
Abstract: New catechol-containing chemical entities have been investigated as matrix metalloproteinase inhibitors as well as antioxidant molecules. The combination of the two properties could represent a useful feature due to the potential application in all the pathological processes characterized by increased proteolytic activity and radical oxygen species (ROS) production, such as inflammation and photoaging. A series of catechol-based molecules were synthesized and tested for both proteolytic and oxidative inhibitory activity, and the detailed binding mode was assessed by crystal structure determination of the complex between a catechol derivative and the matrix metalloproteinase-8. Surprisingly, X-ray structure reveals that the catechol oxygens do not coordinates the zinc atom.